The Bidirectional Value Return of Education and Technology: The Review and Integration Path of Intelligent Education - Wang, Wei; Li, Panpan; Zhang, Lixin (Journal of Theory and Practice in Education and Innovation, 2025)
With the development of artificial intelligence, technology applications have gradually penetrated into educational scenarios. The application of artificial intelligence in the field of education, education is advertised by the pronouns of “efficiency”, “precision” and “individuality”. However, technology is a double-edged sword. The educational application of technology should be carried out under the premise of fully respecting the value of education, and should not be constrained by the “efficiency”, “precision” and “individuality”. Based on the analysis of the alienation phenomenon in the application of artificial intelligence, this article conducts a reflection on the return to the origin of education from the perspectives of ontology, axiology, life theory and technology theory. Finally, it is proposed that education in the era of artificial intelligence should adhere to the people-oriented nature of education, respect the experience of life growth, focus on students’ experiential learning, form a diversified evaluation orientation of generative learning, realize the Bidirectional value return of artificial intelligence and education, and promote the healthy growth of individual life.